SIFAT FISIK, KIMIA DAN ORGANOLEPTIK NUGGET KEONG SAWAH DENGAN BAHAN PENGISI PATI TEMU IRENG - Tri Listiana; Joko Teguh Isworo (Universitas Muhammadiyah Semarang, 2012)
Snails fields is a type of freshwater snails and easy to find in the rice fields, ditches, and lakes. This animal is widely consumed in various regions of Southeast Asia and has good nutritional value because they contain high protein. Starch is made of extraction of Curcuma aeruginosa roxb, starch component retrieval is 49.56% so it has the potential to be extracted and used as a starch source material. The purpose of this research is to know elasticity, protein content, moisture content, fat content and flavor nuggets snail fields based on the addition of starch as filler Curcuma aeruginosa roxb retrieval. Variations addition of starch is carried out snails field (K): starch of Curcumaaruginosa roxb (P) (K100: P0, K80: P20, K75: P25, K70: P30, K65: P35, K60: P40, K55: P45). The research design used was Completely Randomized Design (CRD). Results indicated the highest elasticity in starch concentration of 45% is 14.94 N / mm, protein content in starch concentrations of 0% (48.4%), fat content at a concentration of 45% (30.03%), water content at 0 % (15.30%). Results favorite flavor nuggets snail with substitution K55: P45 with a value of 2.86 and substitution ofproducts with K100: P0 has the smallest value that is equal to 2.43.Keywords: snails field nuggets, starch of Curcuma aeruginosa roxb, quality